Analisis Nilai-Nilai Pendidikan Agama Islam Dalam Web Drama Korea “Lunch Box, Surat yang Lezat” - Husnul Mar'iyyah; Santi Andriani (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study aims to analyze the values of Islamic Religious Education as represented in the Korean web drama “Lunch Box, Surat yang Lezat” as a product of global popular culture. This study departs from the limitations of previous research, which has generally positioned Korean popular culture as a phenomenon that potentially erodes religious values, without sufficiently considering the presence of educational messages aligned with Islamic principles. This research employs a qualitative approach using content analysis to examine the storyline, dialogues, characters, and visual symbols presented in the web drama. The findings indicate that “Lunch Box, Surat yang Lezat” represents several Islamic values relevant to Islamic Religious Education, including compassion, honesty, responsibility, simplicity, hard work, and respect for others. These values are constructed implicitly through narrative elements, enabling the development of moral awareness among viewers without adopting a doctrinal approach. The novelty of this study lies in its integration of Islamic Religious Education with popular culture analysis, particularly Korean web dramas, which remain relatively underexplored in the Indonesian academic context. Theoretically, this study contributes to strengthening the media literacy paradigm within Islamic education by viewing popular media as a potential pedagogical space. Practically, the findings offer implications for Islamic Religious Education educators in designing contextual, critical, and adaptive learning strategies that respond to the dynamics of students’ digital cultural environments.